Hand–arm vibration and outcomes of surgery for Dupuytren's contracture. (9th June 2021) - Stirling, P H C; Ng, N; Jenkins, P J; Clement, N D; Duckworth, A D; McEachan, J E
Abstract: Background: Dupuytren's contracture was recently designated a prescribed occupational disease when it occurs in patients with previous hand–arm vibration (HAV) exposure. Aims: The aims of this study were to describe the impact of self-reported HAV exposure on upper limb function and satisfaction following surgery for Dupuytren's contracture. Methods: Paired pre- and postoperative Quick version of Disabilities of the Arm, Shoulder and Hand (QuickDASH) and patient satisfaction questionnaires were prospectively collected from all patients undergoing surgery for Dupuytren's contracture over a 6-year period. Patients self-reported HAV exposure duration. Results: Results were available for 425 hands (65%) at mean 13 months postoperatively. There were 111 patients (26%) that reported HAV exposure. The prevalence of HAV exposure was significantly greater in male compared with female patients (32% versus 4%; P < 0.001). A statistically significant difference in preoperative (difference 7.47; 95% confidence interval 4.78–10.17; P < 0.001) and postoperative QuickDASH score (difference 6.78; 95% confidence interval 2.69–10.88; P < 0.001) was observed between the two groups, but difference in QuickDASH improvement was not significantly different (difference 1.76; 95% confidence interval −1.58 to 5.10; P > 0.05). No significant difference in satisfaction rate or return to work was observed between the two groups. Conclusions: Previous HAV exposure influenced the pre and postoperative function in patients undergoing surgery for Dupuytren's contracture, but had no effect on satisfaction or return to work. Further prospective research will be required to determine whether the introduction of a compensatory framework will have a more profound effect on the functional outcomes of surgery.